006: DEVELOPMENT OF BEST PRACTICE GUIDELINES FOR MANAGEMENT OF PREVALENT COMMUNITY DISEASES. (24th August 2015) - Sia:Pharmacology, Isidro C; Caragay, Ruben N; Estifania, Edna; Lam, Hilton Y; Madamba, Jennifer S; Velasco, Dulce Corazon; Villena, Maria Fatima Adalid; Tumbagahan, Sahreen Dee; Imbat, Vincent H
Abstract : Background: Poor Filipino families have yet to experience equity and access to critical health services. To alleviate this problem, Community Managed Health Programs (CMHPs) build their capability for self-directed development through an education process that has contributed to enhancing people's democratic processes of governance. Through their CMHP, the community re-discovers their traditional/indigenous healing practices, making these an integral part of their health services in addition to the use of biomedicine at the primary level of health care. However, there is a need to develop guidelines that are evidence-based and that can be used by CMHPs as providers of promotive, preventive, curative and rehabilitative services that are effective, accessible, available and acceptable to the community. In the process, CMHPs have the potential to become an extension of the existing formal local health system. Objectives: The general aim of the project is to establish the best practices guidelines (BPGs) for the management of top ten diseases based on the experiences of CMHPs as an essential component of their services in providing poor communities equitable access to essential health services. Methods: Archival research and writeshop-consultations were undertaken to produce the BPGs and validated by more than a hundred Community Health Workers, NGO-based health practitioners, national and local government health professionals and academics. Result: Best practice guidelines were developed for eight communicable diseases-common cold/cough, influenza, measles, pulmonary tuberculosis, acute gastroenteritis, amoebiasis, scabies, intestinal parasitism; and two non-communicable diseases-diabetes and hypertension. Conclusion: Validated BPGs were produced. These will be subjected to further studies like laboratory (to determine active ingredients and mechanisms of action) and community-wide supervised and documented clinical trials (funded by e.g. PITAHC) that can be the next steps, aside from extensive literature review from international sources.